PEMBERDAYAAN KEPEMIMPINAN DANYON DALAM MENINGKATKAN PROFESIONALISME PRAJURIT DI BATALIYON GUNA MENGHADAPI TANTANGAN KONTEMPORER : (Studi Kasus di Bataliyon Arhanud-3/YBY) - Aulia R. Mahar; Surya Wibawa Suparman (PT. Data Jaringan Visual Indonesia (Djava), 2026)
This research aims to analyze the empowerment of Battalion Commander (Danyon) leadership in enhancing soldier professionalism to face contemporary challenges. These challenges include the development of military technology, non-conventional threats such as hybrid warfare and cyberattacks, as well as rapidly changing geopolitical dynamics. The study examines how Danyon applies transformational leadership to shape soldiers who are resilient, adaptive, and equipped with both technical and moral competencies. Through a qualitative research method with a case study approach, this research collects data from in-depth interviews with Danyon and soldiers, field observations, and document analysis related to training and unit operations. The findings show that effective Danyon leadership can significantly improve soldiers' motivation, discipline, and capability to face modern challenges. Moreover, mental development and soldier welfare are crucial factors in supporting unit combat readiness. The discussion also highlights the essential role of technological adaptation and resource management in maintaining professionalism and operational effectiveness within the unit.